Monotherapy with stenting in subarachnoid hemorrhage (SAH) after middle cerebral artery dissection. (8th April 2015) - Puri, Ajit S; Gounis, Matthew J; Massari, Francesco; Howk, Mary; Weaver, John; Wakhloo, Ajay K
Abstract : Isolated middle cerebral artery dissection is a rare clinical entity, with descriptions limited to a few case reports and case series. Symptomatic dissection in the anterior circulation can present as an ischemic stroke in a young population; however, it is rarely associated with subarachnoid hemorrhage. We describe a young patient who presented with acute headache from a subarachnoid hemorrhage that was ultimately determined to be due to a vascular dissection in the middle cerebral artery. The initial angiogram showed vascular irregularities in this area with stenosis. Repeat imaging 4 days after presentation identified a pseudoaneurysm proximal to the stenosis. The patient was successfully treated with a self-expanding nitinol stent and followed up with serial angiography during postoperative recovery in the hospital; additional angiograms were performed approximately 1 and 6 months after treatment. Serial angiograms demonstrated incremental healing of the dissection. The patient was discharged and remains neurologically intact at the 6-month follow-up.